The RAPID Consortium: A Platform for Clinical and Translational Pituitary Tumor Research - Karsy, Michael; Kshettry, Varun; Gardner, Paul; Chicoine, Michael; Fernandez-Miranda, Juan C.; Evans, James J.; Barkhoudarian, Garni; Hardesty, Douglas; Kim, Won; Zada, Gabriel; Crocker, Tomiko; Torok, Ildiko; Little, Andrew (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives Pituitary tumor treatment is hampered by the relative rarity of the disease, absence of a multicenter collaborative platform, and limited translational–clinical research partnerships. Prior studies offer limited insight into the formation of a multicenter consortium.Design The authors describe the establishment of a multicenter research initiative, Registry of Adenomas of the Pituitary and Related Disorders (RAPID), to encourage quality improvement and research, promote scholarship, and apply innovative solutions in outcomes research.Methods The challenges encountered during the formation of other research registries were reviewed with those lessons applied to the development of RAPID.Setting/Participants RAPID was formed by 11 academic U.S. pituitary centers.Results A Steering Committee, bylaws, data coordination center, and leadership team have been established. Clinical modules with standardized data fields for nonfunctioning adenoma, prolactinoma, acromegaly, Cushing's disease, craniopharyngioma, and Rathke's cleft cyst were created using a Health Insurance Portability and Accountability Act-compliant cloud-based platform. Currently, RAPID has received institutional review board approval at all centers, compiled retrospective data and agreements from most centers, and begun prospective data collection at one site. Existing institutional databases are being mapped to one central repository.Conclusion The RAPID consortium has laid the foundation for a multicenter collaboration to facilitate pituitary tumor and surgical research. We sought to share our experiences so that other groups also contemplating this approach may benefit. Future studies may include outcomes benchmarking, clinically annotated biobank tissue, multicenter outcomes studies, prospective intervention studies, translational research, and health economics studies focused on value-based care questions.
Keywords: pituitary adenoma; craniopharyngioma; Cushing's disease; Rathke's cleft cyst; registry; consortium